Parecer n. 00005/2019/CNCIC/CGU/AGU - Brasil. Controladoria-Geral da União (CGU), Costa, Cristiane Souza Braz (My University, 2019)
Acordo de Cooperação Técnica
Keywords: Consultoria Jurídica; UNIDADE::GABINETE DO MINISTRO (GM); ASSUNTO::Consultoria Jurídica